2021
DOI: 10.3390/bios11020048
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Electroactive Halophilic Bacteria for Improvements and Advancements in Environmental High Saline Biosensing

Abstract: Halophilic bacteria are remarkable organisms that have evolved strategies to survive in high saline concentrations. These bacteria offer many advances for microbial-based biotechnologies and are commonly used for industrial processes such as compatible solute synthesis, biofuel production, and other microbial processes that occur in high saline environments. Using halophilic bacteria in electrochemical systems offers enhanced stability and applications in extreme environments where common electroactive microor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 91 publications
(155 reference statements)
1
7
0
3
Order By: Relevance
“…Current density production was observed at a negative potential (-0.16 V/SHE) after two or three days of polarization. This is in agreement with the results of Torres et al (2009) and Gaffney et al 2021, who observed a faster start-up at lower potentials when marine sediments were used as inoculum. Maximum current density peaks were reached after 16 days of polarization.…”
Section: Halotolerant Bioanode Growthsupporting
confidence: 93%
“…Current density production was observed at a negative potential (-0.16 V/SHE) after two or three days of polarization. This is in agreement with the results of Torres et al (2009) and Gaffney et al 2021, who observed a faster start-up at lower potentials when marine sediments were used as inoculum. Maximum current density peaks were reached after 16 days of polarization.…”
Section: Halotolerant Bioanode Growthsupporting
confidence: 93%
“…Biohybrid electrochemical systems, where biological catalysts are coupled to abiotic electrodes, represent a sustainable approach for a variety of technological applications spanning from biosensing and water quality monitoring, bioelectrosynthesis, and micro to low power generation. Additionally, the use of photosynthetic entities as the biocatalyst allows utilizing sunlight, one of the most attractive energy sources, to power such systems, paving the way to the field of semiartificial photosynthesis. Using whole, metabolically active, microorganisms greatly simplifies the preparation of the biocatalyst (no enzyme isolation/purification required) and potentially enhances stability of the system thanks to their self-repairing and replication features. Purple nonsulfur bacteria have been used as model organisms for studying bacterial photosynthesis. , Additionally, purple bacteria are of great interest for their potential application for H 2 synthesis, , as well as bioremediation and biosensing, with Rhodobacter capsulatus ( R. capsulatus ), representing a very interesting candidate as biophoto­catalyst due to their extreme metabolic versatility .…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of microorganisms' metabolism has increased the reaction’s efficiency [ 7 , 8 ]. The use of MFCs for electricity production is still not optimized, and the amount of electric current generated by this system is low; however, the potential of such systems is great.…”
Section: Introductionmentioning
confidence: 99%